Systematic Aspects of Terminology - Espanha Gomes, Hagar; de Almeida Campos, Maria (Meta, 1996)
AbstractThis article describes terminological research in Brazil. The authors present their own research, covering some aspects of the General Theory of Terminology (GTT) namely the concepts of "concept" and concept system.